Efficiency of PT Kalbe Farma's Financial Performance in Driving Digital Transformation for Business Growth - Puput Diah Anggraini; Imronudin (IECON: International Economics and Business Conference, 2023)
The purpose of this study is to understand the financial operations of PT Kalbe Farma Tbk. by analyzing financial data using ratios of liquidity, solvency, and rentability. Data being analyzed is the financial statements for business finances covering Balance sheet, Profit/ Loss, and Cash flow PT Kalbe Farma Tbk. from 2020 to 2022. In this quantitative study, data from PT Kalbe Farma Tbk's financial transactions were analyzed using information from Bursa Efek Indonesia. The financial data being provided is a timeline covering the years 2020 through 2022. The current data analysis employs the ratios of likuidity, solvability, and rentability.